Teatr i wychowanie (Theatre and Upbringing) Authors: Krzysztof Homa, Justyna Sprutta, Weronika Pudełko, Katarzyna Skulska - Kalbarczyk, Adam (Poznańskie Studia Teologiczne, 2021)
The book Teatr i wychowanie (Theatre and Upbringing) by Krzysztof Homa, Justyna Sprutta, Weronika Pudełko and Katarzyna Skulska presents the history of the theatre, its essence, typology, as well as the role of the theatre in upbringing and therapy, especially for children. This book demonstrates, among others: • Greek mysteries as the beginning of the European theatre, • the history of the theatre in the world and Poland, • the school theatre in the past and present, • the essence of the theatre, as well as theatrical and paratheatrical genres. Moreover, in this book examples of paintings presenting the theatre are displayed. The reviewed book is a multi-author monograph.